2015
DOI: 10.1002/lt.24104
|View full text |Cite
|
Sign up to set email alerts
|

Serostatus following live attenuated vaccination administered before pediatric liver transplantation

Abstract: After liver transplantation (LT), live attenuated vaccines (LAVs) are generally contraindicated. LAVs are recommended before LT for patients 6 months of age. However, the evidence supporting this practice is limited. Patients were enrolled before and after LT. Clinical data for patients were obtained from medical records. Serum antibody titers were evaluated at the time of enrollment and prospectively. Serum antibody titers were measured with a hemagglutination inhibition test for measles and rubella and with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
23
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(23 citation statements)
references
References 23 publications
0
23
0
Order By: Relevance
“…[19][20][21] In a study by Funoki et al of children undergoing liver transplant, the seropositivity rates after live vaccination pre-liver transplant were 47% for measles, 49% for mumps, and 68% for varicella. 22,23 Finally, even in those children who enter transplant with protective antibodies, immunosuppressive medications may result in waning immunity over time. 5,7,[24][25][26] In a study of pediatric liver transplant recipients who entered liver transplant immune to measles and varicella, 22% lost immunity to measles and 63% lost immunity to varicella between two to seven years post-transplant.…”
Section: Discussionmentioning
confidence: 99%
“…[19][20][21] In a study by Funoki et al of children undergoing liver transplant, the seropositivity rates after live vaccination pre-liver transplant were 47% for measles, 49% for mumps, and 68% for varicella. 22,23 Finally, even in those children who enter transplant with protective antibodies, immunosuppressive medications may result in waning immunity over time. 5,7,[24][25][26] In a study of pediatric liver transplant recipients who entered liver transplant immune to measles and varicella, 22% lost immunity to measles and 63% lost immunity to varicella between two to seven years post-transplant.…”
Section: Discussionmentioning
confidence: 99%
“…Only 47% of vaccine recipients remained measles seropositive at that time. 103 Other studies have similarly shown either poor seroconversion pretransplant or loss of measles antibody posttransplant. 79,104 Of note the clinical significance of seroreversion is unclear, as patients with seroreversion may still possess cell-mediated measles-specific immune memory.…”
Section: Pretransplant Mmr Vaccinationmentioning
confidence: 97%
“…In a prospective vaccine study in pediatric liver transplant recipients, 49 patients received pretransplant measles vaccine and measles serostatus was measured a median of 21 months posttransplant. Only 47% of vaccine recipients remained measles seropositive at that time . Other studies have similarly shown either poor seroconversion pretransplant or loss of measles antibody posttransplant .…”
Section: Measlesmentioning
confidence: 99%
“…The NCCHD has an original vaccination protocol for LT recipients before and after LT. 11 LT candidates received polio vaccinations before their scheduled transplantation according to the NIP in Japan.…”
Section: Institutional Polio Vaccine Administration Protocolmentioning
confidence: 99%